Going regional: Distributional effect of taxes and transfers in six EU countries and the UK - Chrysa Leventi; Margarita Katsimi; Panos Tsakloglou (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2022)
Within a context of extended periods of financial crises, regional income inequality and poverty have emerged as topics of substantial policy interest. Taxes and social transfers represent some of the most important policy instruments that governments have in their disposal for the mitigation of economic disparities. The aim of this paper is to analyse the distributional effect of taxes and transfers at the regional level in Czechia, Greece, Spain, France, Italy, Poland and the UK. Using microsimulation techniques, we provide descriptive statistics and estimates of the impact of 2019 tax-benefit policies on poverty and within and between-region inequality. Within-region inequality is found to be the primary explanatory factor of total inequality in all countries studied. Taxation policies do not seem to be able to change the within/between structure of inequality, even in countries with strong regional elements in their income tax policies. Our findings underline the importance of well-designed policies that address territorial inequalities and promote spatial justice, especially in the lowest income regions.
Keywords: 330; Microsimulation; Taxation; Welfare Benefits; Regional Economics